INTESTINAL OBSTRUCTION DUE TO ASCARIS LUMBRICOIDES, CASE REPORT - Suror, Mohammed; Miskeen, Elhadi; Almushly, Rehab; Albalal, Muowya; M.Elhasan, Elhasan; Yousif, Nasr Eldin; Imam, Mohamed; Eldirdiri, Sami (مجلة الجزيرة للعلوم الصحية; مجلد 6 عدد 1 (2010), 2010)
Ascaris lumbricoides, an intestinal roundworm, is one of the most common helminthic human infections worldwide ( 1 ) . It is estimated that more than 1.4 billion people are infected with A. lumbricoides, representing 25 percent of the world population (2) .The highest prevalence of ascariasis occurs in tropical countries where warm, wet climates provides environmental conditions that favor year-round transmission of infection. This contrasts to the situation in dry areas where transmission is seasonal, occurring predominantly during the rainy months )3( .The prevalence is also greatest in areas where suboptimal sanitation practices lead to increased contamination of soil and water. The majority of people with ascariasis live in Asia (73 %), Africa (12 %) and South America (8 %), where some populations have infection rates as high as 95 % (4 , 5) . The majority of infections with A. lumbricoides are asymptomatic. However, the burden of symptomatic disease worldwide is still relatively high because of the high prevalence of disease. Clinical disease is largely restricted to individuals with a high worm load (1)